Gonioscopy findings and prevalence of occludable angles in a Burmese population: the Meiktila Eye Study. Issue 7 (18th June 2007) - Casson, R J; Newland, H S; Muecke, J; McGovern, S; Abraham, L M; Shein, W K; Selva, D; Aung, T
Abstract : Aim: To determine the prevalence of preglaucomatous angle-closure disease in central Myanmar. Methods: A population-based survey of inhabitants ⩾40 years in the Meiktila District was carried out; 2481 subjects were identified, 2076 participated and 2060 underwent gonioscopy of at least one eye. Eyes with angles traditionally described as "occludable" were recorded as primary angle-closure suspects (PACS); eyes with PACS and peripheral anterior synechiae (PAS), or an increased intraocular pressure but without primary angle-closure glaucoma, were recorded as primary angle closure (PAC). Results: The prevalence of PACS in at least one eye was 5.7% (95% CI 4.72 to 6.62); prevalence increased with age and was more common in women (p<0.001). The prevalence of PAC in at least one eye was 1.50% (95% CI 1.47 to 1.53). All participants with PAS had at least 90° of closure (range 90–360°). Conclusion: The prevalence of preglaucomatous angle-closure disease (PACS and PAC) in this population was 5.7% and 1.5%, respectively. PACS was more common in women, and its prevalence increased with age.